English, Irish and subversives among the dismal scientists - Allington, Nigel F. B.; Thompson, Noel W., 1951- (Emerald, 2010)
This volume presents commissioned essays on important, but often neglected, Irish and English economists of the 18th and 19th centuries. Noticeable papers include Tom Sowell on Observations on Certain Verbal Disputes and Sam Hollanders extended essay on Samuel Bailey, which adds to his voluminous treatment of the great classical economists. This volume intends to bring much needed attention back onto forgotten economists that shaped economic history.
Keywords: Economics -- History.; elektronické knihy; electronic books